Reshaping the U.S. cattle industry: producers and packers, 1914–1933 - Gresham, Daniel T. (Kansas State University, 2019)
In 1914 the stockmen of the American West launched what they referred to as the "war on the packers." Desiring more than rhetoric, stockmen donated their own money to finance a producer-led investigation of the big meat packer’s economic power. That investigation ultimately led to a Federal Trade Commission bombshell report that indicted the packers for attempting to control the global food supply, served them a crippling consent decree, and ended with the Packers and Stockyards Act in 1921. Perennial conflict is historians' standard narrative of the relationship between producers and packers. However, from 1922 to 1933, producers such as John Kendrick, Dan Casement, and O. M. Plummer, cooperated with Thomas E. Wilson and other big packers along associational lines and looked to packers for industry leadership. Although contemporary producers and packers applauded their newfound cooperative attitudes, producers never fully trusted the packers, making this a tenuous cooperation. The political philosophy of associationalism helped legitimize big packer leadership of the industry. Producers' acceptance of packer leadership is evident in their shared effort to reform the practices of meat retailers, how producers generally supported packer policies, and how they worked through the Federal Farm Board to eliminate middlemen. The packers also created a campaign for increased consumer consumption of meat and cast vegetarians as their common enemy as a way of unifying the livestock industry. The big packers and the National Live Stock and Meat Board used their power in subtle and often hidden ways to get producers to raise smaller cattle and get consumers to purchase more meat and to prepare it in certain ways. The producers largely accepted the packers demand for smaller cattle. Finally, the Meat Board relied on several consumer-based networks established by home economists, but these women were employees—not actual members of the board. While board members respected the home economist’s ability and advice, institutionally they were junior partners of sorts in the industry collective known as the Meat Board. As employees, home economists of the board were not expected to defend housewives’ consumer choices, but to shape those choices. The Meat Board’s home economics department members attempted to shape consumer thought by manipulating as many channels to the consumer as possible, from schools to women’s magazines. On the eve of the New Deal then, many big producers stood ready to follow packer leadership.
Keywords: U.S. cattle industry; American West; Meat packers; Food supply; National Live Stock and Meat Board; Consumer